2013
DOI: 10.2139/ssrn.2294110
|View full text |Cite
|
Sign up to set email alerts
|

Mining Big Data Using Parsimonious Factor and Shrinkage Methods

Abstract: A number of recent studies have focused on the usefulness of factor models in the context of prediction using "big data" (see e.g., Bai and Ng (2008), Dufour and Stevanovic (2010), Forni et al. (2000, Kim and Swanson (2014), Stock and Watson (2002b, and the references cited therein). We add to this literature by analyzing the predictive bene…ts associated with the use of independent component analysis (ICA) and sparse principal component analysis (SPCA), coupled with a variety of other factor estimation and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 100 publications
0
11
0
Order By: Relevance
“…A detailed explanation of the above two methods is given in a supplemental Appendix available as Supporting Information. Recursive and standard principal component analysis (RPCA and OPCA). PCA is widely used to estimate factors or diffusion indices in large data environments (see Kim & Swanson, (), and references cited therein). In this paper, we utilize PCA, called OPCA in our later discussion of our empirical findings to differentiate it from recursive PCA (discussed below).…”
Section: Estimating Diffusion Indexesmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed explanation of the above two methods is given in a supplemental Appendix available as Supporting Information. Recursive and standard principal component analysis (RPCA and OPCA). PCA is widely used to estimate factors or diffusion indices in large data environments (see Kim & Swanson, (), and references cited therein). In this paper, we utilize PCA, called OPCA in our later discussion of our empirical findings to differentiate it from recursive PCA (discussed below).…”
Section: Estimating Diffusion Indexesmentioning
confidence: 99%
“…In the context of high‐frequency data, are measures of risk such as so‐called realized volatility useful as predictors? Finally, are alternative “sparse” diffusion index methodologies, such as sparse principal components analysis and independent component analysis, useful in real‐time prediction (see, e.g., Kim & Swanson, )?…”
Section: Introductionmentioning
confidence: 99%
“…where y t is a scalar, x t is a (N 1) vector of predictors, and is (N 1) vector of unknown parameters. In matrix notation, let y be a (T 1) vector, X be a (T N ) matrix and " be a (T 1) component analysis and sparse PCA (Kim and Swanson, 2014b), combining forecast PC (Huang and Lee, 2010), principal covariate regression (e.g. Tu and Lee, 2013).…”
Section: Estimation Methodsmentioning
confidence: 99%
“…Banerjee et al (2014) present forecasts using a factor-augmented error correction model. Comparisons and reviews of various factor forecasting models can be found in Eickmeier & Ziegler (2008) and Kim & Swanson (2013).…”
Section: Final Commentsmentioning
confidence: 99%